Pengaruh Serangan 9/11 terhadap Perkembangan Dinamika Keamanan Internasional - Ni Luh Bayu Purwa Eka Payani (Andalas Journal of International Studies (AJIS), 2016)
The 9/11 took place fifteen years ago yet still becoming one of theworst tragedies in American history. This also changed the face ofinternational security. Before terrorist attack became headlines in allinternational news networks, states all over the world still concerned about conventional security where war could only conducted by states. Now, states especially western states need to face the challenge come from non-states threat. To see what changes the terrorist attack in New York brings to international security, here I will explain three major effects. The three effects are based on American Foreign Policy towards terrorism which was adopted by almost countries; the emergence of Global War on Terrorism, Regime Termination in Afghanistan and Iraq, and World Focus on Jihadist Movement by Al-Qaeda and ISIS. By using explainative method, these indicated variables will explain how 9/11 changed the face and the dynamic of international security.Keywords: 9/11, terrorism, international security, regime termination, jihadist movement.